Isolation of bioactive compounds from the petroleum ether soluble fraction of Eichhornia crassipes (Mart.) Solms flowers with dual evaluation: In silico studies of isolated molecules and in vitro/in vivo activities of the extract - Md. Mirazul Islam; Suriya Akter Shompa; Hasin Hasnat; Safaet Alam; Saima Jahan Riti; Ferdousy Kabir; Md. Sakhawat Hossain; Mohammad A. Rashid (PLoS ONE, 2026)
Eichhornia crassipes (water hyacinth), an invasive aquatic plant, has attracted interest as a potential source of pharmacologically active natural products despite its ecological impact. The present study investigated the petroleum ether soluble fraction (PSF) of the methanolic extract of E. crassipes flowers to identify bioactive constituents and evaluate their biological activities. Chromatographic isolation followed by ¹H NMR spectroscopy led to the identification of five compounds: Kaempferol (Compound 1), Luteolin (Compound 2), Stigmasterol (Compound 3), 4-carboxybenzyl alcohol (Compound 4), and 4-methoxybenzaldehyde (Compound 5). Antimicrobial activity was assessed using disc diffusion and minimum inhibitory concentration (MIC) assays, thrombolytic activity through an in vitro clot lysis method, and antidiarrheal activity using the castor oil–induced diarrhea model in mice. Molecular docking and ADMET analyses were performed to explore potential target interactions and pharmacokinetic characteristics. The PSF exhibited moderate antimicrobial activity, with the highest inhibition against Bacillus subtilis (20.33 ± 1.25 mm) and MIC values ranging from 15.6–500 μL/mL. The extract also produced 14% clot lysis in the thrombolytic assay. In vivo antidiarrheal testing showed dose-dependent inhibition, reaching 38.89% reduction in diarrheal count at 600 mg/kg, approaching the activity of loperamide. Molecular docking analysis revealed that the identified compounds exhibited potential binding affinities comparable to standard ligands, suggesting potential interactions with relevant biological targets. The stigmasterol showing the highest interaction toward the κ-opioid receptor (−10.3 kcal/mol), comparable to loperamide (−9.1 kcal/mol). Flavonoids such as kaempferol and luteolin demonstrated notable binding with antimicrobial targets including dihydrofolate reductase (DHFR) and β-ketoacyl-ACP synthase (KAS), as well as thrombolytic target tissue plasminogen activator (TPA). ADMET predictions indicated favorable drug-likeness for the flavonoids but highlighted lipophilicity-related limitations for stigmasterol. Collectively, these findings highlight the PSF of E. crassipes as a promising reservoir of multi-target phytochemicals with potential applications in gastrointestinal, infectious, and thromboembolic disorders.